EFEKTIVITAS PENERAPAN TERAPI GUIDED IMAGERY TERHADAP KECEMASAN DAN TANDA-TANDA VITAL PADA PASIEN PRE-KATETERISASI JANTUNG: LITERATUR REVIEW - Fa'iz Medica Putra; Yosi Oktarina; Andika Sulistiawan; Dini Rudini; Febri Tri Andini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Coronary heart disease remains one of the leading causes of mortality worldwide. Cardiac catheterization is a commonly performed diagnostic and therapeutic procedure for patients with this condition. However, patients scheduled for cardiac catheterization often experience anxiety, which may affect vital signs such as blood pressure, heart rate, and respiratory rate, thereby increasing the risk of procedural complications. Guided imagery is a non-pharmacological nursing intervention that can reduce anxiety and stabilize vital signs through activation of the parasympathetic nervous system, promoting relaxation. This literature review aims to analyze the effectiveness of guided imagery therapy in reducing anxiety and stabilizing vital signs in patients undergoing pre-cardiac catheterization, based on evidence-based practice from studies published within the last seven years. A systematic literature search was conducted using PubMed, Google Scholar, ProQuest, and Indonesian journal repositories. Keywords included guided imagery, anxiety, cardiac catheterization, and vital signs. Inclusion criteria were articles published between 2017 and 2025, written in English or Indonesian, and focusing on guided imagery interventions in cardiovascular patients or anxiety-related conditions. A total of 15 articles were reviewed, consisting of 10 national and 5 international journals. All studies demonstrated that guided imagery therapy significantly reduced anxiety levels (p<0.05) and improved vital sign stability. Anxiety reduction ranged from 25% to 40%, with significant improvements in systolic blood pressure (10–15 mmHg), heart rate (8–12 bpm), and respiratory rate (3–5 breaths per minute). Guided imagery therapy is an effective, safe, easy-to-implement, and cost-effective non-pharmacological nursing intervention for reducing anxiety and stabilizing vital signs in patients prior to cardiac catheterization. Its implementation may enhance the quality of care and reduce procedural complications.